Guidelines for the Transmission of Cultural Values and Collective Identity : Chili Pastes of Southeast Asia - Chakamanont, Sirin; Tubporn, Hatairath; Ruengrong, Akhawit (Journal of Cultural Approach, 2022)
The purpose of this research are 1) to analyze the values and collective identity associated with the Southeast Asia’s chili pastes; 2) to analyze the cultural inheritance; and 3) to present guidelines for the transmission of Southeast Asia’s cultural inheritance. The scope of this research focuses on chili pastes uses as dips: Namprik in Bangkok, Thailand; Jeawbong in Luangprabang, Laos; and Tik Kreoung in Phnom Penh, Cambodia, as case studies. The research methods include documentary research, interviews with chili paste and food culture experts, and field research in the corresponding areas. The interviews were in-depth and semi-structured. The key informants were divided into three groups: academics, community leaders, and community members who continued producing the chili paste. There were a total of 60 interview participants, which were comprised of 15 participants in Thailand, 15 participants in Laos, and 30 participants in Cambodia. The analyzed data was used for drafting, reviewing and presenting the guidelines for the transmission of cultural values and collective identity of Southeast Asia’s chili pastes. The research resulted are as follows: 1) the values and collective identity associated with Southeast Asia’s chili paste were found and divided into five areas: (1) history reflecting the identity of Southeast Asian roots; (2) aesthetics reflects a minimalist identity; (3) ethics reflecting on identity of love and care; (4) wisdom reflecting harmonization with nature; and (5) a way of life reflecting Southeast Asian living practices. 2) The cultural inheritance of values and collective identity associated with Southeast Asia’s chili pastes is transmitted through lifelong learning, which is a combination of formal education (vocational schools and universities), non-formal education (restaurants and cooking schools), and informal education (learning through direct experiences in households and communities. 3) The guidelines for transmission of cultural inheritance should focus on the family unit as a fundamental platform for integrating intangible cultural heritage into lifelong learning. A person who takes care of a child is the key to success of passing on this taste of wisdom through everyday practices.